Criminalistic characteristic of acts of terrorism and its importance in investigation - Arenova, L.K.; Nabiyeva, Ye.A. (KSU Publ., 2018)
This article is dedicated to determination of consent of criminalistic characteristic of criminal acts, as well as to identification of criminalisticsally significant, evidentiary and orienting information in each single case that allows organizing their qualitative detection. Authors show that criminalistic characteristic of acts of terrorism is aimed to reflect, broadly, peculiarities of commitment of concerned socially-dangerous acts, and in more specific consideration – to define regular mutually conditioned connections between its elements with the aim of advancement of particular typical investigative leads as a basis for investigation forming according to a defined program. The act of terrorism must be considered from the perspective of its dominant elements: the identity of the criminal as part of the criminalistic characterization of an act of terrorism committed by self-incrimination (suicide bomber); the relationship of the method, the crime under investigation to the situation under which a socially dangerous act is committed. Cognition process during criminal investigation can be presented as an algorithm of consistent achievement of constantly forming tasks, emphasizing of which compiles investigation differentiation into certain stages, where its features and content are identified.
Терроризм актілерін криминалистік сипаттау жəне оның тергеудегі маңызы
Криминалистическая характеристика актов терроризма и ее значение в расследовании
Keywords: criminalistic characteristic of criminal acts; identification of criminalisticsally significant; evidentiary and orienting information in each single case that allows organizing their qualitative detection; of criminalistic characteristic as a person